New Voices from Intersecting Identities Among International Students Around the World: Transcending Single Stories of Coming and Leaving - Koo, Katie; Mathies, Charles (Journal of International Students, 2022)
In this article, we introduce our special issue, “International students’ lived experiences in the era unprecedented uncertainty and challenges: New voices from intersectional identities.” Our motivation and intention for this special issue, the focus, and the overall methodological approach are discussed. In addition to presenting the contributions of each article to this issue, we also discuss what we (all authors of this special issue) try to talk and how our voices are reflecting our unique experiences of coming to the new counties and leaving where we lived as international students by unfolding our stories and multiple identities that are intersecting while we experienced.